Pengaruh Model TGT Berbasis Math Relay Race terhadap Kemampuan Operasi Hitung Bilangan Cacah Siswa SD - Nadia Haeriska; Karin Auliani; Khosyi Anindya Chotimah; Thalytha Majma Tsaqifa Taftazani; Dina Kristin Harefa; Hafiziani Eka Putri (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2026)
This study was motivated by the low level of engagement and ability in performing integer arithmetic operations among elementary school students in mathematics learning. One approach that can be taken to address this issue is to implement a learning model that is active, enjoyable, and promotes student collaboration. This study aims to determine the effect of the Teams Game Tournament (TGT) learning model based on the Math Relay Race on the ability of elementary school students to perform integer arithmetic operations. This study employs a quantitative approach using a one-group pre-experimental design (pretest-posttest). The sample consisted of 20 fourth-grade elementary school students selected using purposive sampling. The research instruments comprised open-ended questions administered before and after the intervention. Data were analyzed using a normality test, a Paired Sample t-Test, and an N-Gain test. The results indicate an improvement in students’ skills following the implementation of the TGT learning model based on the Math Relay Race. This is evidenced by the results of the Paired Sample t-Test, with a significance level of < 0.05, indicating a significant difference between pretest and posttest scores. Additionally, the N-Gain test yielded an average of 0.5366, which falls into the moderate category. Learning through games and teamwork made students more active, enthusiastic, and motivated in participating in mathematics lessons.